Wear characteristics of titanium and its alloy TI-6AL-4V - Tay, Jiang Han. (2011)
Titanium and its alloy have been widely exploited in the aerospace industry and medical field due to its high strength-to-weight ratio and excellent corrosion resistance. However, its poor wear mechanical properties have set many researches and articles to focus on enhancing its surface properties like thermal oxidation, nitrogen ion implantation and carburization technology. A general study of Ti-6Al-4V replacement in medical field due to the presence vanadium is also covered in the literature review. The main interest of this report however focus on factors that contribute to titanium’s wear properties like its low d-bonding, the high number of slip system due to its crystal structure, its high friction coefficient and affinity environmental condition. Two experiments based on dry sliding of Ti-6Al-4V against itself and harder material AISI M2 steel was studied in this report. Observations on the thermal effects and surface microstructures are being concluded and also to support a general wear concept in untreated Ti-6Al-4V.